Housing, health and happiness: How inadequate housing shapes child and parental wellbeing - Laurence, James; Russell, Helen; Smyth, Emer (ESRI, 2024)
There has been a good deal of attention in Irish policy discourse to housing supply and affordability. However, there has been less focus on the extent to which the quality of housing impacts the wellbeing of children and their parents. This study addresses this gap in knowledge by using data from Growing Up in Ireland (GUI) Cohort ’08 to explore the influence of housing and neighbourhood quality on parental and child wellbeing. In particular, it looks at how the length of time households have spent experiencing inadequate housing can shape families’ wellbeing. The study adopts a multidimensional approach to measuring inadequate housing, capturing whether the home is unsuitable (in terms of size or problems like damp), whether the household struggles to adequately heat the home, lack of access to a garden or play space, the number of residential moves and the type of tenure. In addition, neighbourhood quality is assessed in terms of local disorder, having low social capital (with few family and friends in the area) and having access to fewer local services. Child wellbeing is measured using the Strengths and Difficulties Questionnaire (SDQ), which captures the extent of children’s socio-emotional difficulties.